Analysis of Determinants of Type 2 Diabetes Mellitus: A Literature Review - Adzkiya Safitri; Yuanita Windusari; Iche Andriyani Liberty (Indonesian Journal of Global Health Research, 2026)
Type 2 Diabetes Mellitus (T2DM) is a global health issue, with 537 million cases reported in 2021 and projected to increase to 783 million by 2045. Indonesia ranks fifth globally, with T2DM prevalence rising to 8.5% in 2018. The high number of cases and the risk of severe complications, such as heart disease, stroke, and kidney failure, underline the need for an in-depth study of risk factors to mitigate the disease's impact. Objective to further examine the determinants of Type 2 Diabetes Mellitus. This study employed a literature review approach using search engines such as Google Scholar, PubMed, ScienceDirect, and BMC with the keywords "Risk Factor" AND "T2DM." The reviewed articles are reputable and accredited, published within the last five years. From a total of 20 reviewed articles, the findings indicate that Type 2 Diabetes Mellitus is significantly associated with factors such as age, gender, hypertension, physical activity, family history of diabetes, obesity, smoking, cholesterol levels, fruit and vegetable consumption, and sweet food consumption. The determinants of Type 2 Diabetes Mellitus include physical activity, dietary patterns, family history of diabetes, BMI, smoking, age, gender, hypertension, and cholesterol levels.